2022
DOI: 10.1038/s41598-022-21825-w
|View full text |Cite
|
Sign up to set email alerts
|

Gustatory function of sensilla chaetica on the labial palps and antennae of three tortricid moths (Lepidoptera: Tortricidae)

Abstract: In adult Lepidoptera the labial palps are best known for their role in CO2 detection, but they can also bear sensilla chaetica which function is unknown. The number and distribution of sensilla chaetica in labial palps was studied using a bright field microscope. To determine if these sensilla have a gustatory function, we performed single sensillum electrophysiology recordings from palp and antennal sensilla of adult moths of Cydia pomonella (L.), Grapholita molesta (Busck) and Lobesia botrana (Denis and Shie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 64 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…The diurnal and nocturnal species (G. molesta and C. pomonella, respectively) are closely related and belong to the same tribe, Grapholitini, whereas the crepuscular species (L. botrana) belongs to the tribe Olethreutini (Fagua et al, 2017). As in other phytophagous lepidopterans, adults of these species do not feed because they rely on larval nutritional reserves (Wäckers et al, 2007;Amat et al, 2022). Consequently, reports of flower visiting are occasional and only in L. botrana (Benelli et al, 2023a), and so detecting flower cues does not appear to be essential to them.…”
Section: Introductionmentioning
confidence: 99%
“…The diurnal and nocturnal species (G. molesta and C. pomonella, respectively) are closely related and belong to the same tribe, Grapholitini, whereas the crepuscular species (L. botrana) belongs to the tribe Olethreutini (Fagua et al, 2017). As in other phytophagous lepidopterans, adults of these species do not feed because they rely on larval nutritional reserves (Wäckers et al, 2007;Amat et al, 2022). Consequently, reports of flower visiting are occasional and only in L. botrana (Benelli et al, 2023a), and so detecting flower cues does not appear to be essential to them.…”
Section: Introductionmentioning
confidence: 99%
“…As for sensilla chaetica, we found that the L1 proximal surface had a higher density than the L3 distal surface in all three species. Electrophysiology experiments have shown that SCh has both mechanoreception and gustatory functions [19,79,80]. Given the presence of SCh on only external surfaces of the antennal club (L1 proximal and L3 distal), it may suggest either a mechanical or gustatory (non-olfactory) function in the dung beetles evaluated in this study.…”
Section: Discussionmentioning
confidence: 82%
“…In insects, antennae are the primary sensory organ and house different types of sensilla classified primarily on their external morphology [17,18], performing various functions such as olfaction, gustation, mechanical reception, thermoreception and hygroreception [19][20][21][22][23]. The morphology and function of an antenna can be defined by the ecological niche occupied; this niche is subjected to selective pressure, influencing chemical communication and thereby increasing the signal-perceiving efficiency [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Our heatmap result showed that GR1 , GR2, and GR3 were the top three highest expressing receptors in labial palps, which were responsible for CO 2 sensing; thus, the projection from the labial palp into the brain was mainly for CO 2 sensing. But we also found that there are other GRs also expressed in the labial palp, which may be related to wider sensing of different cues [ 41 ]. And previous research has suggested that bilateral projections enable olfactory receptor neurons (ORNs) to release an asymmetric amount of neurotransmitters on both sides of ALs [ 42 ], which leads to a stronger signal in one projection neuron (PN) than in the other, enhancing the contrast of odor concentration gradients between the two brain hemispheres [ 43 ].…”
Section: Discussionmentioning
confidence: 99%